Adrenal gland non-Hodgkin's lymphoma in a patient with pulmonary adenocarcinoma. (15th May 2013) - D'Antonio, Antonio; Addesso, Maria; Caleo, Oliviero; Caleo, Alessia
Abstract : Although primary neoplasms of adrenal gland are uncommon, adrenal metastases are frequently encountered in patients with malignancy, and lung is the most common primary tumour site. Among primary tumours of the adrenal gland non-Hodgkin's lymphoma (NHL) is a very rare entity. We describe a case of a 79-year-old man with a previous diagnosis of adenocarcinoma of the lung who presented after 2 years with a unilateral adrenal gland mass. A solitary metastasis from pulmonary carcinoma was suspected and a laparoscopic adrenalectomy was performed. Histological examination revealed a diffuse large B-cell NHL. The patient was treated with CHOP regimen plus rituximab and a total remission was achieved. After an 8-month follow-up the patient was free of disease. This is the first reported case of a rare non-synchronous tumoral combination involving lung and adrenal gland, emphasising at the incidental discovery of the NHL during a procedure performed for a pulmonary adenocarcinoma.